Di corpi permeabili e sguardi mimetici. Costruire il sé in utero - Miglio, Nicole (Aesthetica Preprint, 2023)
Contemporary debates dealing with visualization technologies in the reproductive process tend to view ultrasound outcomes as a way of reducing the maternal self to a mere container. The focus of this body of studies is mostly on the representation of the fetus – whose ‘independence’ from the maternal body is discussed – and the ways in which biomedical technologies have eliminated the pregnant subject, omitting its presence from fetal iconography. In this paper, I argue for broadening the field of analysis, decentering it somewhat from the mere representation of the conceptus, to investigate instead the conditions of possibility of the construction “in images” of the fetus. The hypothesis in the background of the present reflection is that the imaginative and technological production of the fetus has, in the Western history of ideas and knowledge-power practices that shape human reproduction, an exemplifying role in the mutual movement between visualization and subjectification. In the first section of my paper, I discuss the most prominent features of maternal imagination, by highlighting its biopolitical dimension and aesthetic meaning; in the second, I address the relationship between imagination, imaginary and image through Christoph Wulf’s theory of mimesis. The maternal imagination can be understood within a socially shared imaginary of beliefs that afford women an active role in the process of pregnancy— especially, in the outcomes of gestation. This interpretive paradigm has little to do with the contemporary overemphasis on the iconicity of the fetus, but much to offer to my working hypotheses: the complex and equivocal relationship between the agency of image, imaginary, and technology (in the sense of technê and technological device) is not exclusive to contemporary visualization but innervates the history of the maternal body and human reproduction.